Investigating the molecular mechanism of iguratimod act on SLE using network pharmacology and molecular docking analysis - Zeng, Huiqiong; Chen, Shuai; Lu, Xiaoping; Yan, Zhenbo (Frontiers in Bioinformatics, 2022)
Objective Iguratimod (IGU) is a novel small disease-modifying compound widely used in Asia for the treatment of rheumatic diseases. IGU is a methane sulfonanilide. We applied a network pharmacology to investigate the pharmacological mechanisms of IGU act on SLE . Methods We used pharmmapper, UNIPRO, and OMIM databases to screen the potential active compounds of IGU, and the potential action targets of the compound were predicted. Hub target genes among the intersections of the potential targets (IGU) and related genes (SLE)was validated using PPI network generated by String database. Go and KEGG enrichment analysis was carried out through David online platform. Finally, the molecular docking of hub targets and their corresponding compounds were completed through Autodock Vina and PyMOL software. Result A total of 292 potential active components of IGU compounds, 6501 potential disease targets of SLE and 114 cross targets were screened from the above database. Network topology analysis identified 10 hub targets, such as CASP3, AKT1, EGFR, MMP9, and IGF1. Go enrichment analysis mainly focusing on the negative regulation of apoptotic process and signal transduction. KEGG enrichment analysis illustrated that the PI3K-AKT signaling pathway, MAPK signaling pathway, and FoxO signaling pathway might play a signiﬁcant role in SLE. Molecular docking confirmed that the active compounds of IGU had strong binding activity to the hub target. Conclusion This study based on network pharmacology and molecular docking validation preliminarily revealed the protein targets affected by IGU acting on SLE through , and explored potential therapeutic mechanism role of IGU in SLE treatment by multi-pathways.